2010
DOI: 10.1097/bcr.0b013e3181cb8cea
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients With Necrotizing Fasciitis

Abstract: Patients who survive an episode of necrotizing fasciitis are at continued risk for premature death; many of these deaths were due to infectious causes such as pneumonia, cholecystitis, urinary tract infections, and sepsis. These patients should be counseled, followed, and immunized to minimize chances of death. Modification of other risk factors for death such as obesity, diabetes, smoking, and atherosclerotic disease should also be undertaken. The sex difference in long-term survival is intriguing and needs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…However, it is an important finding that one-half of all deaths within 1 year of presentation were late and followed the first month of presentation. Similar observations of significant numbers of late deaths have been made by others in a number of conditions not limited to severe sepsis and septic shock [7,19], necrotizing fasciitis [20], pneumonia [21][22][23], and endocarditis [10,24]. These data support the notion that longer terms of outcome may give a better appreciation of burden of illness and argues for use of 90-day or 365-day outcomes in clinical trials [6,7].…”
Section: Discussionsupporting
confidence: 71%
“…However, it is an important finding that one-half of all deaths within 1 year of presentation were late and followed the first month of presentation. Similar observations of significant numbers of late deaths have been made by others in a number of conditions not limited to severe sepsis and septic shock [7,19], necrotizing fasciitis [20], pneumonia [21][22][23], and endocarditis [10,24]. These data support the notion that longer terms of outcome may give a better appreciation of burden of illness and argues for use of 90-day or 365-day outcomes in clinical trials [6,7].…”
Section: Discussionsupporting
confidence: 71%
“…Nekrotizan fasiit tanısıyla izlenen 44 olgunun klinik değerlendirmesi ğer hastalığı nekrotizan deri yumuşak doku enfeksiyonlarında risk faktörleridir. [1,3,4,6,8] Çalışmamızda DM %52,2 oranında en sık rastlanan risk faktörü olarak ortaya konulmuş, bunu travma ve operasyonlar izlemiş-tir. Liu ve arkadaşları [7] nekrotizan fasiit tanısıyla 87 hastanın incelendiği çalışmalarında benzer olarak hastaların %50,6'sında risk faktörü olarak DM tespit ettiklerini bildirmişlerdir.…”
Section: Discussionunclassified
“…Ülkemizde yapılan çalışmalarda mortalite oranları %14,3-33,3 arasında değişmektedir. [5,6,10] Light ve arkadaşları [8] nekrotizan fasiitli hastaların uzun dönem sonuçlarını bildirdikleri çalışmalarında mortalite oranlarını çalışma-mızla aynı oranda (%25) bildirmişlerdir. Klasik bilgi olarak %80'lere ulaşabilen mortalite oranlarının bizim ve benzer çalışmalarda bu düzeye ulaşmaması, günü-müzde hızlı bir yaklaşımla uygun antibiyoterapilerin uygulandığını ve erken geniş cerrahi debridmanların yapıldığını düşündürmektedir.…”
Section: Discussionunclassified
“…Although the patient was on his way to recovery his concerns about providing for his family should he die were justifiable as a study by Light et al 22 showed that the life expectancy of a cohort of patients discharged from hospital who previously had NF was shorter than gender and age matched controls. These findings are not entirely surprising as increasing age is associated with impaired immunity 23 The presence of comorbidities such as diabetes increases the risk of a fatal outcome of those affected by NF 2,3, Post-hospitalization, patients with NF were prone to die from infectious diseases other than NF.…”
Section: Psychological Support and Long-term Follow-upmentioning
confidence: 96%